2009
DOI: 10.1002/app.31287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of experimental parameters on the formation of chitosan–poly(acrylic acid) nanofibrous scaffolds and evaluation of their potential application as DNA carrier

Abstract: Gene delivery from tissue engineering scaffolds has demonstrated the ability to promote gene transfer and stimulate new tissue formation. In this article we report a novel nanofibrous scaffold based on polyelectrolyte complexes as a vehicle for delivery of DNA. When polycation chitosan (CS) was dropped into polyanion poly(acrylic acid) (PAA) suspension and freeze‐dried, CS‐PAA nanofibrous scaffold with diverse microstructure would be formed under different experimental conditions. The nanofiber size was affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…These parameters vary according tothe preparation conditions (volume ratio of CS to PAA, final suspension pH, concentration and molecular weight of CS, incubation time and reaction temperature). Nanofibers can bind plasmid DNA very well and show a potential to enhance gene transfer in tissue engineering applications [ 136 , 137 ].…”
Section: Polyelectrolyte Complexesmentioning
confidence: 99%
“…These parameters vary according tothe preparation conditions (volume ratio of CS to PAA, final suspension pH, concentration and molecular weight of CS, incubation time and reaction temperature). Nanofibers can bind plasmid DNA very well and show a potential to enhance gene transfer in tissue engineering applications [ 136 , 137 ].…”
Section: Polyelectrolyte Complexesmentioning
confidence: 99%
“…Electrospinning has been used to fabricate controlled-release systems to deliver small molecule drugs (Jiang et al 2005;Cui et al 2006;Huang et al 2006;LuongVan et al 2006;Stitzel et al 2006;Taepaiboon et al 2006;Feng et al 2010;Okuda et al 2010), proteins (Reilly and Bruner 2004;Wei et al 2006;Zhang et al 2006;Chiu et al 2007;Jin et al 2008;Maretschek et al 2008;Fletcher et al 2009;Ionescu et al 2010), and nucleic acids (Liang et al 2005;Cao et al 2010;Kim and Yoo 2010;Wang et al 2010). Drug release kinetics from the electrospun matrix can be finely tuned by controlling the nanofeatures (size, geometry, architecture) as well as physicochemical properties of the materials (polymer wetting, swelling, and dissolution as well as drug-polymer interactions).…”
Section: Electrospun Fibersmentioning
confidence: 98%
“…Under these conditions, the size of NPs was 0.477 ± 0.008 nm. Particle sizes of approximately [130][131][132][133][134][135][136][137][138][139][140] nm were obtained at other pH values, but yields were lower than 45 %. It was found that purification by dialysis can provoke a drastic change both in the distribution profile and in the particle size of the complex.…”
Section: Cs-mentioning
confidence: 99%